Karyotype and genome size of zoarcids and notothenioids (Teleostei, Perciformes) from the Ross Sea: Cytotaxonomic implications - A. Morescalchi; M. A. Morescalchi; G. Odierna; STINGO, Vincenzo (Polar Biology, 1996)
In the absence of fossils, the origin of Notothenioidei, a perciform suborder dominating the fish fauna of the Southern Ocean, remains conjectural; some morphoecological evidence suggests relationships to zoarcoids. To test this point we have compared the karyotype morphology and genome size of two species of zoarcids from the Ross Sea to those of one species each of the notothenioid families. Artedidraconidae, Bathydraconidae, Channichthyidae and Nototheniidae from the same region. A karyotype of 48, mostly acrocentric, chromosomes, localization of nucleolar organizers on a pair of small dibrachial chromosomes, a genome size of about 3 pg of DNA, characterize both zoarcids; similar features can be found in the karyology of the notothenioids (especially the Nototheniidae). However, all shared characters appear as plesiomorphic in teleost karyology, which does not help in producing new data on the problem of notothenioid relationships.